The Influence of Interval Training Methods on Increasing VO2Max Capacity of Badminton Athletes Sport Activity Unit on The State University of Padang - Muhammad Arnando; Nurul Ihsan (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2021)
This study aims to see the effect of the interval training method on increasing VO2Max capacity. There are many methods that can increase a person's VO2Max Capacity, including the interval training method. This type of research is a quasi-experimental conducted on badminton athletes at State University of Padang. The population of this study was badminton athletes who joined the sport activity unit of State University of Padang badminton, totaling 21 people. The sampling technique in this study used purposive sampling. This technique is carried out based on the consideration of the researcher. So the number of samples in this study was 10 people. The data collection technique used is VO2Max, namely the Bleep Test. The data that has been collected is used to test the hypothesis using the t test. before the t-test is carried out, the analysis requirements test is carried out, namely the normality test and homogeneity ui test. The results of hypothesis testing using t-test statistics can be concluded as follows: The interval method significantly affects the increase in VO2Max capacity where it is obtained tcount (14.18) > t table (2.26) and the mean difference is 2.41. From the results of the analysis, it can be concluded that there is a significant effect of the interval training method on increasing the VO2Max capacity of badminton athletes in the State University of Padang sports activity unit.